Mother tongue education and transition to English medium education in Uganda : teachers perspectives and practices versus language policy and curriculum - Ssentanda, Medadi Erisa (Stellenbosch : Stellenbosch University, 2015)
Thesis (PhD)--Stellenbosch University, 2014.